Macroalgae Diversity in the Intertidal Zone of Ranca Buaya Beach, Ujung Genteng, Sukabumi - Geraldine, Galas; Fitri, Zahra Nisaul; Nurlatifah, Winda; Nasyifah, Della (Biology and Education Journal, 2026)
Macroalgae are multicellular photosynthetic organisms that play an important role in coastal ecosystems. This study aimed to identify the distribution of macroalgae at Ranca Buaya Beach, Ujung Genteng, West Java. Sampling was conducted using the line transect method with a transect length of 20 meters and a width of 20 meters, consisting of 9 quadrats. The line transect was combined with 1 × 1 meter quadrats placed along each transect line. Environmental parameters measured included temperature, pH, total dissolved solids (TDS), resistance, conductivity, hardness, dissolved oxygen, and salinity using a Water Quality Tester. Light intensity at each transect line was measured using a lux meter. The ecological indices calculated were the Shannon–Wiener diversity index, evenness index, and dominance index. The results showed the presence of 6 species belonging to 3 divisions of macroalgae: 3 species of Chlorophyta, 2 species of Rhodophyta, and 1 species of Phaeophyta. The calculation results indicated a Shannon–Wiener diversity index of 1.63, categorized as moderate, an evenness index of 0.91 indicating an even distribution, and a dominance index of 0.21 indicating low species dominance. Environmental factors such as light intensity, depth, and substrate influenced the abundance and distribution of macroalgae in the intertidal zone.